2017
DOI: 10.1016/j.jocn.2017.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Early or late radiotherapy following gross or subtotal resection for atypical meningiomas: Clinical outcomes and local control

Abstract: We report a single institution series of surgery followed by either early adjuvant or late radiotherapy for atypical meningiomas (AM). AM patients, by WHO 2007 definition, underwent subtotal resection (STR) or gross total resection (GTR). Sixty-three of a total 115 patients then received fractionated or stereotactic radiation treatment, early adjuvant radiotherapy (≤4 months after surgery) or late radiotherapy (at the time of recurrence). Kaplan Meier method was used for survival analysis with competing risk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Nevertheless, in accordance with previous studies (11, 15), our study showed a significant survival benefit from PORT for patients undergoing STR, indicating that PORT should be performed for atypical meningioma patients undergoing STR. Although PORT has been routinely recommended for atypical meningioma patients undergoing STR (3, 5), it is surprising that the utilization rate of PORT was only 42.6% in these patients and even lower in the elder patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, in accordance with previous studies (11, 15), our study showed a significant survival benefit from PORT for patients undergoing STR, indicating that PORT should be performed for atypical meningioma patients undergoing STR. Although PORT has been routinely recommended for atypical meningioma patients undergoing STR (3, 5), it is surprising that the utilization rate of PORT was only 42.6% in these patients and even lower in the elder patients.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the patients who die within 1 month after surgery do not have the opportunity to receive postoperative radiotherapy. Including these patients in analyses will lead to an abrupt drop at the beginning of the Kaplan–Meier survival curve of patients not receiving PORT, which can be seen in several previous studies (4, 11, 17). This may result in a false positive result in the comparison of OS between patients receiving and not receiving PORT.…”
Section: Discussionmentioning
confidence: 84%
“…Beyond this study, much research in radiotherapy has been documented in various fields. Takemura et al used the age‐adjusted Charlson comorbidity index to predict the prognosis of laryngopharyngeal cancer patients treated with radiation therapy; Wang et al performed a clinical analysis of recurrence patterns in patients with nasopharyngeal carcinoma treated with intensity‐modulated radiotherapy; and Dohm et al studied the effect of early or late radiotherapy following gross or subtotal resection for atypical meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…The attrition bias was high in 11 studies with missing data because of restriction in follow-up duration or loss to follow-up for analyzing the outcome [ 3 , 10 , 30 , 35 , 36 , 39 – 43 , 45 ]. The risk of reporting bias was high in five studies that did not report the recurrence number or the percentage of each cohort [ 26 , 34 , 37 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%